IS1311 and IS1245 Restriction Fragment Length Polymorphism Analyses, Serotypes, and Drug Susceptibilities of Mycobacterium avium Complex Isolates Obtained from a Human Immunodeficiency Virus-Negative Patient - Dvorska, Lenka (American Society for Microbiology, 2002)
Six isolates of Mycobacterium avium of genotype dnaJ(+) IS901(−) IS1311(+) IS1245(+) and serotypes 6 (n = 1), 6/9, (n = 2), and 9 (n = 3) were obtained within a 5-month period from a human immunodeficiency virus-negative patient treated for tuberculosis. The isolates were identified with PvuII restriction fragment length polymorphism (RFLP) analysis as a single IS1311 RFLP type and six different IS1245 RFLP types. Six separate colonies/clones obtained by subculture from each of the six isolates were tested for MICs of a set of 10 drugs. This report documents the appearance of isolates that are resistant to antimycobacterial drugs as the duration of therapy increases. Because isolates recovered from the patient following longer duration of treatment were more likely to be resistant to more antimycobacterial drugs, we would conclude that there was selection for antimycobacterial drug-resistant isolates. Analyses of all 36 clones identified three IS1311 and 22 IS1245 types forming three clusters. Tests of 105 environmental samples collected in the home and the work place of the patient yielded 16 mycobacterial isolates, of which one M. avium from soil was of genotype dnaJ(+) IS901(+) IS1311(+) IS1245(+) and serotype 2, and the second M. avium from a vacuum cleaner was of genotype dnaJ(+) IS901(−) IS1311(+) IS1245(+) and serotype 9. Overall analyses of the results did not reveal any relation between serotype, RFLP type, and drug susceptibility. Based on the course of the disease in the patient and different serotypes, IS1311 and IS1245 RFLP types of isolates of M. avium we suppose represent polyclonal infection.